2022
DOI: 10.1111/jen.12991
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogenic nematodes for control of the cotton cutworm Spodoptera litura in marigolds

Abstract: Spodoptera litura Fabricius (Lepidoptera: Noctuidae) is a major pest of marigolds in Thailand. It causes severe damage to flower quantity and quality. The most common control method is synthetic insecticides, although this method struggles to control hidden larvae inside flowers or buds and underground pupae. Entomopathogenic nematodes (EPNs) are widely used as biocontrol agents against many foliage and cryptic insects. The virulence of two commercial EPNs strains, Steinernema siamkayai (Stock, Somsook and Rei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…However, the instar larvae of S. litura and S. exigua generally remain on the underside surface of leaves (Hilliou et al, 2021) while EPNs were generally target to the underground pests and trunk borers (Hazir et al, 2001; Shapiro‐Ilan et al, 2006). Many studies showed that EPN successfully killed the two insects in both larval and pupa stages when the EPNs were applied on the right methods in the greenhouse and field conditions (Burana et al, 2022; Noosidum et al, 2016). For examples, fire retardant gel (Barricade®) can improve S. carpocapsae virulence when applied to control S. litura larvae on surfaces such as bark or leaves.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the instar larvae of S. litura and S. exigua generally remain on the underside surface of leaves (Hilliou et al, 2021) while EPNs were generally target to the underground pests and trunk borers (Hazir et al, 2001; Shapiro‐Ilan et al, 2006). Many studies showed that EPN successfully killed the two insects in both larval and pupa stages when the EPNs were applied on the right methods in the greenhouse and field conditions (Burana et al, 2022; Noosidum et al, 2016). For examples, fire retardant gel (Barricade®) can improve S. carpocapsae virulence when applied to control S. litura larvae on surfaces such as bark or leaves.…”
Section: Discussionmentioning
confidence: 99%
“…In marigold farms, the two insects also feed inside flowers or buds and underground pupae. The first and third instar larvae of S. litura were more susceptible to Steinernema siamkayai Stock, Somsook & Reid, whereas S. carpocapsae caused higher mortality in the fifth instar larvae and pupae (Burana et al, 2022). Moreover, S. exigua pupae showed high susceptibility to S. carpocapsae (Kaya & Hara, 1981), and to Steinernema riobrave Cabanillas, Poinar & Raulston (Henneberry et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations